Electronics Skills With Arduino and Raspberry In Undergraduate Research Course - Gómez, LM Fernández; Martínez, A. Camacho (International Journal of Computer Sciences and Engineering, 2020)
This paper outlines the benefits of incorporating the Raspberry PI and Arduino into an undergraduate research course for bachelor`s degree students. In this course, students work in several projects that provide an experience in research and development. In specific it works with electronics components and realized analysis with a variety of instruments. Explanations are made about three small projects implemented during Fall 2019. Our goal and motivation is to provide a hands-on building component and develop of professional and technical skills.